SOCIAL MEDIA AS A THREAT TO NATIONAL SECURITY: A CASE STUDY OF TWITTER IN PAKISTAN (Margalla Papers, 2022)
Social media has evolved significantly over the years while providing strategic platforms for voices to reach billions of people within no time. Accordingly, it has advantages and disadvantages (threats). The nature of threats emanating from social media, especially Twitter, in the context of Pakistan, are mainly in the form of radicalization, glorification of terrorist groups, propagation of violent sub-nationalism and hybrid warfare. Though Pakistan has been relatively active after 2020 in responding to social media challenges, implementing social media regulations remains an issue, especially when most social media platforms are foreign in origin. This paper evaluates the interlinkage of social media and national security in the context of Pakistan while exploring how agents of insecurity and instability exploit social media and what response mechanism the state has placed to mitigate these threats. The paper is a qualitative inquiry using primary and secondary sources to answer these questions. The research findings suggest marginal securitization of social media, albeit without significant implementation. Bibliography EntryAl Abd, Saad. 2022. "Social Media as a Threat to National Security: A Case Study of Twitter in Pakistan." Margalla Papers 26 (2): 96-107.